Identifikasi Faktor yang Berhubungan dengan Kejadian Diabetes Melitus di Kabupaten Konawe Provinsi Sulawesi Tenggara - Rita Irma (Health Information : Jurnal Penelitian, 2019)
Risk factors for hereditary Diabetes Mellitus, lack of exercise, obesity, old age, stress factors, eating too much sweet and fatty foods, lots of foods containing salt, lack of fiber and other unhealthy habits such as smoking and drinking alcohol. The purpose of this study was to determine the factors associated with the incidence of DM in Unaaha Konawe District. This study includes a descriptive analytical study with a cross-sectional study approach. The population in this study is the people in the Unaaha Konawe District, the sub-district with a total of 24,886 people and the sample in the study totaling 60 people. This study showed that obesity was statistically significant with the incidence of diabetes mellitus with p = 0044. Obesity was associated with the incidence of DM, while genetic history, obesity based on BMI, physical activity, carbohydrate intake and fat intake did not correlate with the incidence of diabetes mellitus.